Optimization of a Polycaprolactone (PCL) Scaffold for Islet and Cellular Transplantation. (July 2018) - Wisel, Steven; Faleo, Gaetano; Conkling, Nicole; Chang, Ryan; Stock, Peter; Desai, Tejal; Tang, Qizhi
Abstract : Introduction: Islet transplantation is a proven effective therapy for patients with type 1 diabetes; however, donor shortage limits this therapy to very few patients with brittle diabetes. Stem cell therapies for beta cell replacement are quickly moving toward clinical application, but the optimal transplant site and delivery vehicle remains unknown. Previous studies have shown that three dimensional support and structure improves islet survival and function. To this end, we have optimized a polycaprolactone (PCL) polymer scaffold as a biocompatible delivery system for beta cell replacement. In these experiments, we used mouse islets as a proof-of-concept system, prior to application of the device for stem cell delivery. Methods: PCL scaffolds of varying thickness were evaluated for maximal loading capacity in vitro with 150 mm PLGA fluorescent microspheres and mouse islets. Insulin secretion was tested in vitro using B6 mouse islets in a perifusion chamber (BioRep, Inc., Miami Lakes, FL). For in vivo testing of islet function and survival within the PCL scaffold, 200 syngeneic islets were transplanted to the epididymal fat pad of STZ-induced diabetic B6 mice, either within a PCL scaffold or directly to the epididymal fat pad. Blood glucose was measured in transplant recipient mice three times weekly for 30 days, at which point islet grafts were explanted and mice were monitored for reversion to hyperglycemia. Normal blood glucose was defined as 250mg/dL for all in vivo experiments. Results/Discussion: Thicker PCL scaffolds fabricated to 1.2mm thickness showed higher loading capacity compared to 1mm thick devices (409 versus 305 microspheres, n=6 per device; Figure 1A). slets showed a similar loading pattern, confirming ample carrying capacity of the PCL scaffold. Microspheres distributed within the three-dimensional porosity of the PCL scaffold, as seen by confocal microscopy (Figure 1B). Mouse islets show no limitation or delay in insulin secretion as a result of loading within the PCL scaffold on perifusion testing (data not shown). When PCL scaffolds were loaded with syngeneic islets and transplanted to the epididymal fat pad B6 mice, 8 out of 9 (89%) mice returned to normoglycemia, while 3 out of 9 (33%) control mice receiving free islets to the epididymal fat pad returned to normoglycemia (p=0.041; Figure 2). Upon explant of islet grafts from normoglycemic mice at day 30, all mice subsequently returned to hyperglycemia, confirming function of the transplanted islets. Conclusions: Our optimized PCL scaffold supports islet survival and function in a syngeneic B6 mouse model, and may provide a delivery system for future stem cell-based beta cell replacement. Research reported in this publication was supported in part by an NIAID T32 training grant from the National Institutes of Health under an award to the University of California, San Francisco (T32AI125222). Figure. No caption available. Figure. No caption available.